Polígonos especiales de interés social y estrategias técnicas de articulación en el cantón Riobamba - Miguel Ángel, Sandoval Iñaguazo (2022)
ABSTRACT: This study aims to determine the special polygons of social interest and technical strategies of articulation of the canton Riobamba. The territorial components allow a sustainable urban representation between the special polygons of the city's social welfare. The occupation and land use of the polygons of social interest were analyzed, considering the PEIS "El Troje" as a case study. The research approach was based on the quantitative, non-experimental, descriptive, explanatory, correlational, documentary, and field method; for which the unit of analysis of this study was considered the Special Polygon of Social Interest "El Troje," where surveys were applied to 305 properties, who contributed with updated information to this research. The results were processed in the IBM SPSS 2.2 program for the dependent variable (technical articulation strategies) and the independent variable (spatial polygons of social interest); the level of confidence of the surveys applied was demonstrated with Cronbach's Alpha, resulting in the concern of the inhabitants belonging to the PEIS of the city of Riobamba. They do not have access to essential services to improve their quality of life. Finally, there were stablished strategies for the articulation of the Polygons of Social Interest based on the municipal ordinance 012 - 2019 of the city of Riobamba, for which defined action competencies were selected for the GADM Riobamba to achieve in the future within 30 years, establishing an urban territory with a safe and spatially sustainable habitat.